Prospective comparative study of hypospadias surgical repair with and without the use of fibrin sealant - Nabil, Ahmad; Sultan, Tamer A.; Shenishn, Mohammed Z.; Fakhry, Tamer (International Surgery Journal, 2019)
Background: Hypospadias is the most common congenital malformation of the penis, affecting about 4-6 males per 1000 male births, and ranging in severity from a urethral meatus that is slightly off-center to a meatus in the perineal area, The aim of this study was to evaluate whether the application of fibrin sealant over the suture lines of neo-urethra reduces complications and improve overall outcome in children hypospadias repair.1,2 Methods: It was a prospective comparative study conducted in a tertiary care center (Department of pediatric surgery - Menoufia University), we included the patients age more than 6 months and less than 4 years presented with hypospadias to our department in this study. A total 30 patients of coronal, sub coronal, mid shaft hypospadias and distal hypospadias were studied and were divided into two groups, group (A) 15 cases and group (B) 15 cases. All patients underwent a tabularized incised plate (TIP) repair with a Dartos vascularized pedicle flap to cover the neo-urethra, In group (B) a thin layer of fibrin sealant applied over the suture line of neo-urethra but no sealant was used in group (A). Results: Postoperative surgical complications: urethra cutaneous fistula, flap dehiscence, flap necrosis and urethral stricture were recorded. Urethrocutaneous fistula flap dehiscence and flap necrosis were lower in group (B) patients. There was no significant difference in postoperative urethral stricture between two groups. Conclusions: Use of fibrin sealant in hypospadias repair is safe and can reduce complications.